A coupled MMALE-FE method for solving 3D fluid-solid interaction problems with multi-material flow. Issue 8 (7th October 2019) - Chen, Xiang; Zhang, Xiong
Abstract : Purpose: The simulation of the fluid–solid interaction (FSI) problem is important for both academic studies and engineering applications. However, the numerical approach for simulating the FSI problems is a great challenge owing to the large discrepancy of material properties and inconsistent description of grid motion between the fluid and solid domains. The difficulties will be further increased if there are multiple materials in the fluid region. In these complicated applications, interface reconstruction, multi-material advection and FSI must be all taken into account. This paper aims to present an effective integrated work of multi-material arbitrary Lagrangian Eulerian (MMALE) method, finite element (FE) method and the continuum analogy method to simulate the complex FSI problems involving multi-material flow. The coupled method is used to simulate the three-dimensional CONT test and the blast-plate interaction. The numerical results show good agreement with the benchmark and the experiment data, which indicates that the presented method is effective for solving the complicated FSI problems. Design/methodology/approach: MMALE and FE methods are used to simulate fluid and solid regions, respectively. The interfacial nodes of fluid and solid are required to be coincident in the whole simulation so the interacted force can be easily and accurately calculated. To this end, the continuum analogy method is used in the rezoning phase. Findings: The coupled method is used to simulate the three-dimensional CONT test and the blast-plate interaction. The numerical results show good agreement with the benchmark and the experiment data, which indicates that the presented method is effective for solving the complicated FSI problems. Originality/value: To the best of the authors' knowledge, this is the first time that the ALE method, moment of fluid interface reconstruction method, continuum analogy method and the FE method are combined to solve complicated practical problems.